Genetic and physiological mechanism of nanoparticle-based salt stress tolerance in plants - Kumar, Ashish; Karabulut, Fadime; Chandrawanshi, Nagendra (Elsevier, 2024)
Abiotic stresses such as drought, extreme temperature, heavy metals, salt, and ultraviolet radiation are affecting plant growth and development worldwide. Plants respond to abiotic stress in various ways through biochemical, morphological, and physiological changes. Multiple approaches are being used to improve abiotic stress tolerance, including the production of genetically altered cultivars for various genes that are responsible for enhancing plant performance. The research in nanotechnology has accelerated the interest in its application in plant science, health, and the environment. Researchers have identified nanotechnology-based tools to cope with climate change issues, which may benefit plant abiotic stress management. Nanotechnology has been practiced by utilizing nano-engineered catalysts to improve abiotic stress tolerance in plants by increasing water uptake and root hydraulic conductance and managing the differences in the number of proteins associated with oxidation-reduction, stress signaling, ROS detoxification, and hormone pathways. The use of nanoparticles enhances seed germination and seedling growth, physiological functions, and photosynthetic activity by enhancing chlorophyll content, protein, and upregulation of genes, improving the plant’s abiotic stress tolerance potential. Plant abiotic stress management using nanotechnology has been proven in many crop plants, and this chapter discusses the nanomaterials uptake, translocation, accumulation, and effect on the plants in various abiotic stresses. © 2024 Elsevier Inc. All rights reserved.
Keywords: abiotic stress tolerance; Cellular process; drought; heavy metals; nanotechnology; salinity